Hands-on networking fundamentals - Palmer, Michael J. 1948- (Networking (Course Technology, Inc.), 2013)
This title helps readers learn network administration from the ground up. Designed to provide a solid foundation in essential concepts and methods, it covers all of the critical knowledge and skills information technology professionals need to work with network operating systems in a network administration environment